Calculation of the Ionization Cross Sections for Ion – Atom Collision by Using the Cdw-Eis Model. - Eyou, Aileen Y.; Elias, Badal H. (Science Journal of University of Zakho, 2013)
In this paper we calculate total cross sections for proton and alpha particle-impact ionization of neutral atoms H , He, Ne and Ar for the energies ranging from 10keV to 10MeV.Also, we calculate theoretical singly, doubly differential ionization cross sections in collisions between proton particle and helium atoms at different impact energies. The provided theoretical model for the program user is based on quantum mechanical approximations which have proved to be very successful in the study of ionization in ion–atom collisions. is on continuum distorted-wave eikonal-initial-state (CDW-EIS) approximation. The results are in reasonable agreement with available experimental data.